Comparative study between hard bovine gelatin capsule and vegetarian capsule - Mohamed, Farahidah; Paimin, Hafizurrahman; Awang, Mohamed; Abdullah Hazim, Anas (2011)
INTRODUCTION: Objective of this study is to compare in-vitro performance of hard bovine gelatin capsule (BC) and hard vegetarian capsules (VC). Such study is timely for several reasons: 1) to find alternative for animal-origin capsule especially when the issue like Bovine Sponge Encephalitis (BSE) arise; 2) to establish scientific data with regard to comparable performance of VC as compared to BC. The model drug that was used was mefenamic acid as it is one of the most widely used Non-Steroidal Anti-Inflammatory Drugs (NSAIDs).